Barriers Affecting Promotion of Active Transportation: A Study on Pedestrian and Bicycle Network Connectivity in Melbourne’s West - Isaac Oyeyemi Olayode; Hing-Wah Chau; Elmira Jamei (Land, 2024)
In the last few decades, the promotion of active transport has been a viable solution recommended by transportation researchers, urban planners, and policymakers to reduce traffic congestion and improve public health in cities. To encourage active transport, it is important for cities to provide safe and accessible infrastructure for pedestrians and cyclists, as well as incentives for individuals to choose active modes of transportation over private vehicles. In this research, we focused on the suburb of Point Cook, located within the City of Wyndham in Melbourne’s west, owing to its rising human population and private vehicle ownership. The primary aim of this research is to examine the barriers in the interconnectivity of active transport networks for pedestrians and cyclists and to determine the segments of the transportation network that are not accessible to Point Cook residents. Our methodology is enshrined in the use of Social Pinpoint, which is an online interactive survey platform, and ground surveys (face-to-face interviews). In our assessment of the suburb of Point Cook, we utilised the concept of 20-min neighbourhoods to evaluate the accessibility of many important places within an 800-metre walking distance from residents’ homes. Based on our online interactive survey findings, approximately one-third of the individuals engaged in regular walking, with a frequency ranging from once a day to once every two days. One-third of the participants engaged in walking trips once or twice a week, whereas the remaining two-thirds conducted walking trips less frequently than once a week. Almost 89% of the participants expressed varying levels of interest in increasing their walking frequency. The findings showed that improving pedestrian and cycling networks that are easily accessible, well-integrated, inclusive, and safe is a prerequisite for achieving active transport and create neighbourhoods in which everything is accessible within a 20-min walking distance.